Possibilities of blitz-psychograms as a tool for human resource management in the supporting system of hardiness of company - Pritvorova, T.; Tasbulatova, B.; Petrenko, E. (Entrepreneurship and sustainability issues, 2018)
The article describes the psychogram method as a tool for human resource management. The article describes the psychogram method as a tool for human resource management, the use of which is provided by the availability of platform technologies in the modern digital economy. The presence in the market space of firms that provide platform services for complex psychological diagnosis enables the manager to adequately assess the required behavioral competencies of the applicant, using as a standard the system of basic parameters corresponding to this position. The system of basic parameters is formed on the basis of the method of blitz-psychogram after passing by professional employees of this firm professional tests based on platform technologies. This allows the company to identify the character traits, motivation, preferred activities and role in the team with efficient employees with minimal own expenses. Applicants who meet the parameters of a psychographic portrait will be internally motivated for this type of activity. This will further reduce the risk of staff turnover, increase the effectiveness of training and the effectiveness of other actions of human resources management by activating the employee's internal motivation in this type of activity.
Keywords: human resource management; psychogram; motivation; behavioral competency; platform technologies